2015
DOI: 10.1021/acsami.5b07804
|View full text |Cite
|
Sign up to set email alerts
|

Double Detection of Mycotoxins Based on SERS Labels Embedded Ag@Au Core–Shell Nanoparticles

Abstract: A sensitive surface-enhanced Raman scattering (SERS) signal dependent double detection of mycotoxins is achieved for the first time, without the aid of nucleic acid amplification strategies. SERS labels embedded Ag@Au core-shell (CS) nanoparticles (NPs) as novel SERS tags are successfully prepared through a galvanic replacement-free deposition. SERS tags produce stable and quantitative SERS signal, emerging from the plasmonic coupling at the junction of Ag core and Au shell. SERS tags engineered Raman aptasens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 186 publications
(92 citation statements)
references
References 51 publications
1
89
0
Order By: Relevance
“…[ 5 ] Noticeably, Ag intrinsically possesses the best plasmonic enhancement at visible frequencies in comparison to other noble metal NPs, and Au featured with excellent biocompatible and stability could serve as an outer shell on the surface of Ag NPs. [ 6 ] All these characteristics allow Ag@Au core-shell (CS) NPs to be a natural candidate to generate a gigantic and customized plasmonic CD response, yet little is known about the plasmonic chiro-optical activity of Ag@Au CS NPs. Rationally understanding the dynamic plasmonic CD responses of Ag@Au CS NP assemblies holds promise for fundamental investigation of the real-time coupling of the optical rotation spectral signature in comparison to Ag NP assemblies.…”
Section: Doi: 101002/adma201600369mentioning
confidence: 99%
“…[ 5 ] Noticeably, Ag intrinsically possesses the best plasmonic enhancement at visible frequencies in comparison to other noble metal NPs, and Au featured with excellent biocompatible and stability could serve as an outer shell on the surface of Ag NPs. [ 6 ] All these characteristics allow Ag@Au core-shell (CS) NPs to be a natural candidate to generate a gigantic and customized plasmonic CD response, yet little is known about the plasmonic chiro-optical activity of Ag@Au CS NPs. Rationally understanding the dynamic plasmonic CD responses of Ag@Au CS NP assemblies holds promise for fundamental investigation of the real-time coupling of the optical rotation spectral signature in comparison to Ag NP assemblies.…”
Section: Doi: 101002/adma201600369mentioning
confidence: 99%
“…[5,6] Highperformance SERS substrates require both high sensitivity and good reproducibility. [7] Along with this demand, some novel structures constituted by two or more noble metals, such as core-shell, [8][9][10] multilayer, [11,12] and periodic array, [13] have been designed with the aim to promote the activity of those ordinary In order to solve this contradiction, we designed a composite structure, which is composed of AuNP and AuNS. AuNS was prepared first as a homogeneous, flexible, and 2D substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Given that DNA molecules of different lengths and sequences can be synthesized easily, nanoparticles can be assembled into a designed nanostructure through DNA hybridization or attachment of end-labelled functional groups 1823 . For example, it has been demonstrated that Au-Ag core-shell nanodumbbells 12,13 and plasmonic core-satellite nanostructures can be assembled through DNA hybridization 14,2428 or binding of other linker molecules 2934 . The SERS effects of the nanoparticle-based nanostructures can be optimized by controlling the gaps between adjacent nanoparticles through coating Ag shells around the nanoparticles 1214 .…”
Section: Introductionmentioning
confidence: 99%
“…The SERS effects of the nanoparticle-based nanostructures can be optimized by controlling the gaps between adjacent nanoparticles through coating Ag shells around the nanoparticles 1214 . In addition, when a DNA aptamer is used as a linker to attach two nanoparticles, an analyte-controllable SERS hot spot at the nanogap between the nanoparticles can be created 28,3537 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation